CONSTRUCTION OF LOCAL TAX POLICY THROUGH THE LENS OF AUTONOMY AND FISCAL SELF-RELIANCE: A STUDY OF CENTRAL PAPUA PROVINCE - Johanis M. Ramandey , Johanis M.; Suripatty , Petrus I.; Waroy , Victor Petrus; Wijayatiningsih , Hana Prihatini; Liborang, Hans F.; Latif, Syukriyanto; Tunjanan , Letarius; ., Suryadi; Mangambe, Petrus; Praestuti , Camelia; Angwarmas , Koernelis; Ngantung , Jean Marzel; Tabuni , Yerry L.; Bogar, Deby S.; Dharsono, Wardhana W. (Yayasan Education and Social Center, 2025)
This community service initiative represents the implementation of the Tri Dharma of Higher Education, specifically in the domain of community service, through a collaborative partnership between the Center for Government Management and Policy Studies at Satya Wiyata Mandala University (USWIM) and the Government of Central Papua Province. The collaboration was established with the primary objective of supporting regional capacity development through academic mentorship. The activity was strategically focused on developing the Academic Paper for the Draft Regional Regulation (Raperda) on Local Taxes and Retribution for Central Papua Province. As a newly formed autonomous region, Central Papua Province requires a comprehensive legal foundation to optimize Local Original Revenue (PAD) in accordance with Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. Through this collaborative endeavor, USWIM provides academic contributions in the form of in-depth studies, comprehensive analysis, and technical support in the process of drafting regional regulations, directly supporting efforts to enhance governmental governance and fiscal independence in Central Papua Province